The Role of Religious Architecture in Increasing Tourist Attraction: A Study of a Sample of Visitors to the Shrine of Dhu Al-Kif - Taha Mahdi Mahmood (Peerian Journals Publishing, 2023)
The architectural, cultural, and religious heritage is a rich record of the creativity of nations, an icon of their genius, a memory that preserves their values, a component of their ancient historical identity across the ages, and a symbol of their uniqueness among other cultures and civilizations.
Keywords: Art; Religious Architecture; Tourist Attractions; The Shrine of Dhu Al-Kif